Personality Styles of Dentists Practicing Hypnosis Confirm the Existence of the Homo Hypnoticus - Wolf, Thomas Gerhard; Baumgärtner, Elena; Peter, Burkhard (Frontiers in Psychology, 2022)
Several publications with healthcare professionals, such as psychotherapists, have shown a significant difference in personality styles in practitioners using hypnosis compared to those not using hypnosis. To investigate differences in personality styles, dentists were contacted to participate in a personality-inventory [Personality Style and Disorder Inventory (PSDI)] online survey. Dentists using hypnosis (HYP DGZH) (n = 418) were compared to dentists not using hypnosis (NONHYP DENT) (n = 162). Results show that hypnosis-practicing dentists score significantly higher in the intuitive/schizotypal ST personality style (p < 0.001) compared to non-hypnosis-practicing dentists. Female dentists scored significantly higher in intuitive/schizotypal ST and unselfish/self-sacrificing SL in the HYP DGZH sample but only in unselfish/self-sacrificing SL in the NONHYP DENT sample. The percentage of women was similar in both samples (68.2%; 67.3%). Intuitive/schizotypal ST was found to be the predominant personality style of men who are interested in or use hypnosis, metaphorically so-called “homo hypnoticus.” Within the limitations of this cross-sectional non-interventional observational online-questionnaire study, results expand this notion to the so-called “homo hypnoticus dentalis.” However, further research on the subject is needed to investigate and confirm this personality type in other than the German-speaking DACH countries.